Medicinal plants sold in open fairs of State of Piauí, northeastern Brazil (Research, Society and Development, 2021)
Ethnobotany studies human-nature relationships, seeking information on the uses of plants and medicinal properties. In this context, open fairs play an important organizational and cultural role, ensuring the preservation of customs and characteristics that represent them. This work sought to identify the main medicinal plants sold by free marketers in three cities in southeastern of Piauí. From a semi-structured questionnaire and interviews with stallholders in open markets in the cities of Jaicós, Paulistana, and Picos. We identified 169 plant species belonging to 100 families and 11 ethnospecies. The most representative family was Fabaceae. Shell was the part with the highest commercialization index in two of the three cities. The species with maximum value of relative importance were endro, copaíba and pixuri. There was a greater similarity between the free markets in Paulistana and Picos. All wealth estimators pointed to numbers above those recorded for the three cities, with the addition of at least 38 species expected for the city of Picos.